DEVELOPMENT OF PROBLEM BASED LEARNING-BASED E-MEDIA TO IMPROVE STUDENTS’ MATHEMATICS LEARNING OUTCOMES IN JUNIOR HIGH SCHOOL - Enda Raskita Tarigan; Abdul Hasan Saragih; Sahat Siagian (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Mathematics learning in junior high schools still faces various challenges, particularly in students’ low achievement and difficulties in understanding abstract concepts such as linear equations. This condition is reflected in Indonesia’s low performance in international assessments such as PISA and TIMSS, as well as the low mathematics achievement of students at SMP Swasta RK Fransiskus Xaverius Namorambe. The learning process remains teacher-centered and has not optimally utilized interactive digital learning media. Therefore, this study aims to develop a Problem Based Learning (PBL)-based E-Media using Google Sites to improve students’ mathematics learning outcomes on the topic of Linear Equations. This study employed a Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were eighth-grade students of SMP Swasta RK Fransiskus Xaverius. Data were collected through interviews, observations, validation sheets, questionnaires, and learning outcome tests. Data analysis techniques included validity analysis, practicality analysis, effectiveness analysis, normality and homogeneity tests, and hypothesis testing. The novelty of this research lies in integrating Google Sites with the Problem Based Learning model to create an adaptive, interactive, and student-centered digital learning environment. The developed media is expected to be valid, practical, and effective in improving students’ understanding, motivation, critical thinking skills, and mathematics learning outcomes. This study also provides implications for the development of technology-based mathematics learning media in junior high schools.